The Effects of Inquiry Learning Management Combining with POE Technique Entitled of “Motion and Energy” Toward Learning Achievement and Attitude in Science Subject of Mathayom Suksa III Students at Education Expansion Schools in Sawankhalok District, Sukhothai Province - Teerajangkapichai, Piyaporn; Visavateeranon, Suchin; Chindanurak, Tweesak (Ratchaphruek Journal, 2021)
The research was the study the students’ learning achievement and scientific toward science subject using inquiry learning management with POE technique. The purposes of this research were: (1) To compare students’ learning achievements before and after learning; (2) To compare post-learning achievement scores with the 70 percent score criterion; (3) To compare attitudes towards science subject before and after learning; and (4) To study relative gain score of learning achievement and attitude towards science subject. Sample consisted of 7 Mathayom Suksa III students at Ban Wangreaschool, an education expansion school in Sawankhalok district, Sukhothai province during the second semester of the 2019 academic year, obtained by cluster random sampling. The employed research instruments were learning management plans, a science learning achievement test, and a scale to assess attitude towards science. Statistics employed for data analysis were the percentage, mean, standard deviation, relative gainscore, and sign test. The research findings revealed that (1) the students’ post-learning achievement were significantly higher than their pre-learning counterpart achievements at the .05 level; (2) the students’ post-learning achievement were significantly higher than the 70 percent score criterion at the .05 level; (3) the students’ post-learning attitude towards science was significantly higher than pre-learning counterpart attitudes at the .05 level; and (4) the relative gain score of students’ learning achievements was at high level and the relative gain score of attitudes towards science was at middle-high level.